LATENT STRUCTURE OF MOTOR AND FUNCTIONAL VARIABLES ON A SAMPLE OF CADET FOOTBALL PLAYERS (Fiep Bulletin - online, 2014)
The complexity of the game puts great challenges before football players with respect to their functional and motor abilities, morphology, technical-tactical preparation and psycho-social status. Sensitivity of some developmental phases, especially puberty (cadets,aged 14-16), makes the training process even more demanding. It is essential to understand the characteristics of young football players’ developmental and growth phases and to plan and programme the respective training process accordingly. The purpose of this research was to determine the latent structure of motor and functional characteristics of cadet football players. The sample of subjects comprised 100 football players, cadets of the Croatian First Football League (1.HNL ). The variables used for the assessment of motor and functional abilities included 22 tests (6 agility tests, 3 functional ability tests, 1 shot-type explosive power test, 4 sprint tests and 8 isokinetic force tests). A component model of factor analysis was used to determine the latent structure of motor and functional variables. The background of motor and functional abilities was identified as consisting of five factors: primary agility, endurance, explosive power, isokinetic force and secondary agility.
Keywords: Croatian football; cadets; motor abilities; functional abilities